2007
DOI: 10.1111/j.1540-5826.2007.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining Appropriate Accommodations for Postsecondary Students with Reading and Written Expression Disorders

Abstract: One of the most significant barriers facing postsecondary students with reading and written expression disorders who are eligible to receive specific accommodations is the lack of professional knowledge pertaining to issues surrounding accommodations. Though guided by Section 504 of the Rehabilitation Act of 1973 and the Americans with Disabilities Act, the process by which accommodation decisions are made varies considerably across institutions of higher education. Given the recent rise in litigation surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 36 publications
2
52
0
2
Order By: Relevance
“…In addition, it was found that the support services staff can help increase self-efficacy through setting appropriate and realistic academic goals (Costello & Stone, 2012). Receiving appropriate mental support and being offered exam accommodations can prove critical to postsecondary school success and to the retention of students with LD who are enrolled in higher education institutions (Lindstrom, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was found that the support services staff can help increase self-efficacy through setting appropriate and realistic academic goals (Costello & Stone, 2012). Receiving appropriate mental support and being offered exam accommodations can prove critical to postsecondary school success and to the retention of students with LD who are enrolled in higher education institutions (Lindstrom, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Often, these students require special support in order to adjust academically and socially to college life (Weyandt & DuPaul, 2008). The number of support programs available to college students with LD is expanding, but the services offered vary considerably from institution to institution (Lindstrom, 2007). Assistance can be provided by focusing on the development of the individual learner through counseling, coaching, guiding, and therapy.…”
Section: Institutional Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggested that proper and continued professional development for faculty members would improve the knowledge and attitudes of faculty as well as improve overall campus climate and graduation rates (Lindstrom, 2007;Shaw & Dukes, 2006;Vogel, Holt, Sligar, & Leake, 2008).…”
Section: The Impact Of Idea and Other Legislation On Postsecondary Edmentioning
confidence: 99%
“…When faculty are not prepared to meet the learning needs of students with disabilities, poor graduation rates can be the end result (Lindstrom, 2007;Zhang, et al, 2010). Students reported the perception that faculty can be skeptical regarding the existence of a disability and the need for accommodations (Vogel, Holt, Sligar, & Leake, 2008).…”
Section: The Impact Of Idea and Other Legislation On Postsecondary Edmentioning
confidence: 99%